MODERN COMPUTER NETWORKS: TYPES, SECURITY ISSUES, AND DEVELOPMENT TRENDS - Akhmedova Iroda Nurmukhammedovna; Elvira Rashidovna Tadzhikhodzhaeva; Tulaghanova Guzal Murod qizi; Azamova Saodat Fayzullayevna (Utilitas Mathematica, 2025)
Modern computer networks play a crucial role in the development of digital infrastructure and the global exchange of information. This paper explores the various types of computer networks, including LAN, WAN, MAN, PAN, and wireless networks, outlining their structure, function, and application across different sectors. A particular focus is placed on the growing challenges related to cybersecurity—such as data breaches, malware, phishing attacks, and unauthorized access—which pose serious threats to network stability and user privacy. Additionally, the paper discusses current trends in network development, including the integration of artificial intelligence, the rise of cloud-based networking, software-defined networks (SDN), and 5G technology. These innovations aim to improve network efficiency, scalability, and resilience. The paper concludes by emphasizing the importance of implementing robust security frameworks and ongoing research to address evolving threats in a rapidly changing digital landscape.